The Role of Kazakh Women in the Art of Aitys (Eurasian Journal of Philology Science and Education, 2023)
Aitys is an integral part of the spiritual life of the Kazakh people. This article is devoted to the work of Kazakh poets-girls, who occupy a special place in the history of the development of Kazakh aitys. This genre is one of the most popular and leading in national literature. The article discusses the work of the most prominent representatives who have made a significant contribution to the development of this genre. The object of analysis is the best examples of aitys art from different eras. The article explores the ideological and thematic content of the works of Kazakh poets-girls. It is indicated that poets touch upon social problems that are relevant to society in a particular historical era. The main attention in the work is paid to the study of the heritage of Kazakh poets-girls. It is indicated that poets touch upon social problems that are relevant to society in a particular historical era. The main attention in the work is paid to the study of the heritage of Kazakh poets-girls. The author summarizes and analyzes in detail the vast factual material, revealing the significance of their work for the development of the art of aitys. The article reflects on their contribution to updating the content of this genre. The article points out that the competition between a horseman and a girl occupies a special place in the art of aitys. In the process of research, a comparative analysis of the works of akyns of past eras and the present is carried out. Aitys of the XIX-XXI centuries are considered. The author emphasizes that this genre has undergone significant changes in the level of content and form. The article reveals the influence of globalization on the development of this genre and the consciousness of akyns.